Enantioselective and Synergistic Herbicidal Activities of Common Amino Acids Against Amaranthus tricolor and Echinochloa crus-galli - Nawasit Chotsaeng; Chamroon Laosinwattana; Patchanee Charoenying (Molecules, 2021)
-glutamine was more toxic than the pure forms; however, d-tryptophan exhibited greater activity than racemate and l-isomer, indicating the sign of enantioselective toxicity. The mode of action was unclear, but d-tryptophan caused bleaching of leaves, indicating pigment synthesis of the grass was inhibited. The results highlighted the enantioselective and synergistic toxicity of some amino acids, which relied upon plant species, chemical structures, and concentrations. Overall, our finding clarifies the effect of stereoisomers, and provides a chemical clue of amino acid herbicides, which may be useful in the development of herbicides from natural substances.
Keywords: Allelopathy and phytotoxic interactions; Weed Control and Herbicide Applications; Botanical Research and Chemistry